Correlations between Antioxidant and Biochemical Parameters of Blood Serum of Duroc Breed Pigs - Sergei Yu. Zaitsev; Anna A. Belous; Oksana A. Voronina; Roman A. Rykov; Nadezhda V. Bogolyubova (Animals, 2021)
Correlations between the major biochemical (BC) and antioxidant (TAWSA) parameters of pigs’ blood are necessary to study in order to assess physiological–biochemical status (PhBS), animal health, production, etc. Blood samples were obtained from Duroc breed boars (n = 77), divided into groups 1 (n = 25), 2 (n = 40) and 3 (n = 12), which were fattened for 65, 72 and 100 days, respectively. Significant positive and negative correlations were found between TAWSA and BC parameters of pigs’ blood for group 3: very high in the case of total protein (TP) (−0.75) and aspartate aminotransferase (AST) (−0.79); high in the case of cholesterol (−0.72), glucose (0.66), alkaline phosphatase (0.66), calcium ions (−0.60) and globulins (0.53); moderate in the case of albumins (−0.36), triglycerides (−0.35), magnesium (−0.32) and phosphorus (−0.27). The same was found for group 2: high in the case of TP (0.51); moderate in the case of globulins (0.48), cholesterol (0.33) and phosphates (0.25). The only moderate correlation was found for group 1: magnesium (−0.48), glucose (0.36) and calcium (−0.25). This tendency indicated the stabilization of pig PhBS during growth and fattening, which can be useful for understanding the PhBS and antioxidant features of pigs, the factors of their nutrition, maintenance, etc.